Managing the welfare impacts of urbanization in Zambia: A case for a composite district performance index - Masumbu, Gibson (Graduate School of Development Policy and Practice, 2019)
This paper looks at the evolution of urbanization in Zambia. The country has a population of just over 15 million people with about 35% living in urban areas. The population in the urban areas is projected to increase driven by both natural population growth and rural-urban migration. This population growth is expected to put pressure on the provision of services in urban areas. The country has been implementing a decentralization programme that is meant to devolve vital tasks to the local authority. If this happens, the local authorities will have the pressure of ensuring that people in their cities have decent standards of living. The localized city development index will assist local authorities with information to use in assessing their performance. The index adopts the Alkire Foster multidimensional measurement approach.